Developing Fine Motor Skills in 4–5 Year Old Children through Loose Parts Media at RA Sakila Kerti - Nur Rizki Oktaviana; Moch Bayu Ibrahim S (PT Ilmu Inovasi Nusantara, 2025)
This study describes how loose parts media can enhance the fine motor skills of 4–5-year-old children at RA Sakila Kerti. Using a qualitative case study approach, the research involved direct observation and interviews with teachers. Initially, many children faced difficulties in fine motor tasks, such as pinching small items, gluing, and arranging patterns. However, after participating in loose parts activities like sorting bottle caps, threading straws, and creating collages, children showed significant improvement. They became more skilled in finger control, better focused, and more confident. These activities also encouraged positive social interaction, as children shared materials and helped each other. Teachers played an important role as facilitators, guiding children without limiting their freedom to explore. Loose parts activities support contextual learning and align with the principles of the Merdeka Curriculum. The study concludes that loose parts are not only effective in stimulating fine motor skills but also promote creativity, critical thinking, and independence. These findings provide valuable insights for early childhood educators in designing engaging and meaningful learning activities that support holistic development. Incorporating loose parts into daily learning fosters curiosity and exploration, laying a solid foundation for children’s future academic and life readiness.